2015
DOI: 10.1039/c5ra15601g
|View full text |Cite
|
Sign up to set email alerts
|

Removal of a reactive dye and hexavalent chromium by a reusable bacteria attached electrospun nanofibrous web

Abstract: A contaminant resistant Lysinibacillus sp. NOSK was isolated from a soil sample and its Reactive Black 5 (RB5) and Cr(VI) removal efficiencies were investigated as a function of changes in the initial pH values, temperature, static/shaking conditions, reactive dye and Cr(VI) concentrations. In this study, an electrospun polysulfone nanofibrous web (PSU-NFW) was found to be effective in attachment of bacterial cells. Bacteria attached PSU-NFWs (bacteria/PSU-NFW) have shown highly efficient removal of RB5, as 99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…23 In the present study, we focused on anionic surfactant bioremediation and therefore produced novel biocomposite webs by immobilization of two different SDS degrading bacterial strains on electrospun nCA and pCA webs. It was observed that, bacterial cells strongly immobilized on nCA and pCA brous surfaces, the bacteria immobilized webs exhibited similar biodegradation performances with free STB3 and STB4 cells and can be reused for several cycles of SDS biodegradation with recovery capabilities.…”
Section: Reusability and Applicability Of Stb3/pca And Stb4/ Pca Biocmentioning
confidence: 99%
“…23 In the present study, we focused on anionic surfactant bioremediation and therefore produced novel biocomposite webs by immobilization of two different SDS degrading bacterial strains on electrospun nCA and pCA webs. It was observed that, bacterial cells strongly immobilized on nCA and pCA brous surfaces, the bacteria immobilized webs exhibited similar biodegradation performances with free STB3 and STB4 cells and can be reused for several cycles of SDS biodegradation with recovery capabilities.…”
Section: Reusability and Applicability Of Stb3/pca And Stb4/ Pca Biocmentioning
confidence: 99%
“…The Lysinibacillus sp. NOSK culture isolated from wastewater treatment system [35] was routinely maintained in Nutrient Broth (NB) medium. The working bacterial culture was prepared from the stock culture stored at −20 • C in 70% (v/v) sterile glycerol.…”
Section: Cultivation Of Bacterium In Nutrient Broth (Nb)mentioning
confidence: 99%
“…Adsorption coefficients were estimated via seven isotherm models (Langmuir, Langmuir with linear partitioning, Freundlich, Freundlich with linear partitioning, Generalized Langmuir-Freundlich, Toth, Linear) using the isotherm parameter fitting software IsoFit [35]. The mean of three individual determinations was used to calculate cell counts.…”
Section: Adsorption Isotherms and Kinetics Studiesmentioning
confidence: 99%
“…This is also possible in case of organic materials, which in addition can be processed in an easier way than the inorganic ones, are more flexible for modifications in terms of specific 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 process needs, and are available at moderate cost 8 . In this regard, electrospun organic fibers have become an alternative as microorganism carriers in water bioremediation studies [9][10][11][12][13] . The attention received by this type of synthetic materials has been mainly due to their analogy with natural nanofibrous protein networks (morphology, mechanics and surface chemistry), and their high biocompatibility with human cells 14 , which makes them suitable to be used in human healthcare applications.…”
Section: Introductionmentioning
confidence: 99%